A Convenient Method of Facilitating Aryl–Aryl Bond-Formation Reactions in the Synthesis of Biquinoline- and Quinoline-Bearing Chromene Derivatives - Sankaran, Mathan; Chandraprakash, Kumarasamy; Uvarani, Chokkalingam; Vennila, Kailasam Natesan; Velmurugan, Devadasan; Mohan, Palathurai Subramaniam (Synlett, 2012)
A method to derive functionalized biquinoline- and quinoline-bearing chromene bicyclic systems through aryl–aryl bond formation in a one-pot synthesis is described. The X-ray structure analysis provides insight into the mode of orientation of the molecules and opens the way to the synthesis of various hybrid molecules by making use of suitable substituents at R1, R2, and R3.
Keywords: one-pot synthesis; quinoline; chromene; sulfuric acid; p-toluenesulphonic acid